History of cluster headache - Heiko Pohl (SAGE Publishing, 2022)
Objective: To summarise the history of cluster headache evolving concepts and growing insights. Background: Excruciating pain, activation of the parasympathetic nervous system, and circadian rhythmicity characterise cluster headache attacks. Results: We find the oldest descriptions of patients suffering from the disorder in case reports of the 17th and 18th centuries. Only in the 19th and early 20th centuries did physicians start hypothesizing its cause. Initially, many researchers suspected the origin of the pain in peripheral nerves or blood vessels. However, eventually, they understood that the cause of the disease lies in the brain. In 1998, Positron emission tomography studies revealed increased activity of the posterior hypothalamus, whose role remains incompletely understood. Only recently have researchers realised that being diseased implies more than dysfunction. Recent studies analysed the consequences of cluster headache for each patient. Many struggle to deal with the disorder even in the absence of pain. Conclusion: Physicians have been aware of this type of pain for at least 300 years. Only when researchers studied pathological anatomy and physiology did knowledge accrue. A more comprehensive picture of the disease severity emerged when they also considered its consequences.